Through survivors' eyes : from the sixties to the Greensboro Massacre - Bermanzohn, Sally A., 1947- (Vanderbilt University Press, 2003)
In passionate first-person accounts, Through Survivors' Eyes tells the story of the six survivors of the Greensboro Massacre in 1979.